(untitled) (Medico Legal Update, 2021)
Assess the relationship and diagnostic performance of retinol-binding protein 4 (RBP-4) as a biomarker of diabetic nephropathy (DN) at different levels of albuminuria (normo-, micro- and macro-albuminuria). A case-control study, that involved 185 participants, 47 were healthy control, and 138 diabetic patients (46 were normoalbuminuric patients [NA], 48 patients were microalbuminuria [MiA], and 44 patients were macroalbuminuria [MaA]). All diabetic patients were treated with antidiabetic medication (metformin and/ or oral sulfonylureas), all the participants were interviewed by the researcher, and full medical (history of liver, kidney, lung, and other diseases), and sociodemographic data taken from them and recorded in the questionnaire. In the present study, RBP-4 was 14.08±1.82 ng/ml in the control group, 15.98±3.74 ng/ml in the normoalbuminuria (NA) group, 30.38±6.02 ng/ml in the micro-albuminuria (MiA), and 41.01±5.78 ng/ml for macro-albuminuria (MaA), there was a significant difference between all their groups compared to control (p-value <0.001), and between each other (p-value <0.001) except that no significant difference found between control and normoalbuminuria. In conclusion, RBP4 is an excellent predictor of both microalbuminuria and microalbuminuria, there was an inverse relationship between RBP4 with GFR, which indicate it is a good predictor for the progression of diabetic kidney impairment.